2020
DOI: 10.1002/solr.202000269
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Solar Yarns with 15.7% Power Conversion Efficiency, Based on Electrospun Perovskite Composite Nanofibers

Abstract: A flexible perovskite solar yarn with an impressive active lifetime (>216 h) and an exceptional photon conversion efficiency is prepared under ordinary conditions. The champion device demonstrates an average linear mass density of 0.89 mg cm−1 and can be bent over a loop diameter of 2.5 mm, with a negligible efficiency loss. Photoactive nanofibers composed of a polyvinylpyrrolidone (PVP) central strain and a perovskite phase on the surface (with average grain size of 275 ± 14.3 nm), are prepared by electrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 78 publications
0
44
0
1
Order By: Relevance
“…Thus, the choice of materials should consider the durability and bendability while maintaining high light harvesting. To date, the most widely studied options for FSSC are organic solar cells (OPVs) [ 44–46 ] dye‐sensitized solar cells (DSSCs), [ 47,48,49–55,56–59 ] and perovskite solar cells (PSCs) [ 60–62,63–66 ] ( Table 2 ). The past decades have witnessed a great deal of interest in the fiber‐based PVs based on the latter two material categories.…”
Section: Fiber‐shaped Energy Harvesting Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the choice of materials should consider the durability and bendability while maintaining high light harvesting. To date, the most widely studied options for FSSC are organic solar cells (OPVs) [ 44–46 ] dye‐sensitized solar cells (DSSCs), [ 47,48,49–55,56–59 ] and perovskite solar cells (PSCs) [ 60–62,63–66 ] ( Table 2 ). The past decades have witnessed a great deal of interest in the fiber‐based PVs based on the latter two material categories.…”
Section: Fiber‐shaped Energy Harvesting Devicesmentioning
confidence: 99%
“…The past decades have witnessed a great deal of interest in the fiber‐based PVs based on the latter two material categories. As plotted in Figure 8 , DSSC and perovskite FSSCs correspondingly reached remarkable PCEs of 10.28% [ 59 ] and 15.7%, [ 64 ] respectively, and decent levels of J sc , V oc , and FF, as shown in Figure 8b–d. Apart from photoactive layer, judicious design and selection of contacts, charge transporting layers are required to maintain charge transport and collection.…”
Section: Fiber‐shaped Energy Harvesting Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with polymer and thin-film PVs, PSCs offer better PV performance at a much lower cost. [14,207,208] Progress in fPSCs is remarkable, with PCE as high as 18% and now it is approaching 20%. [209][210][211][212][213][214] Modules on plastic substrates, where series-connected cells were fully monolithically patterned by laser ablation, have reached efficiencies in the %10À15% range depending on size and device architecture.…”
Section: Flexible Devicesmentioning
confidence: 99%
“…In this study, under various conditions of electrospinning voltage and humidity, it demonstrated to be an effective technique of controlling CH 3 NH 3 PbI 3 crystal size, quality, and distribution on poly(vinylpyrrolidone) (PVP) nanofibers. The obtained CH 3 NH 3 PbI 3 -PVP nanofibers, which were engineered under optimized conditions, showed enhanced properties, promoting excellent photovoltaic results [ 73 ].…”
Section: Energy Conversionmentioning
confidence: 99%